Manufacturing and characterisation of a new thermal pre-stressed carbon fibre-reinforced lattice core for sandwich panels. (April 2022) - Flora, Francesco; Pinto, Fulvio; Meo, Michele
Development of high-performance sandwich structures is particularly attractive for aerospace applications, where novel lighter materials and structures are object of extensive research. This work is focused on the design of a new high-performance Carbon FRP core as alternative to traditional periodic prismatic ones. The innovative core is designed as a 2D close-packing pattern of circular cells and manufactured by connecting pre-preg corrugated laminates in specific locations. The corrugated laminates are layered following an asymmetric sequence in order to generate residual thermal stresses within the core to enhance energy absorption and compressive properties. The distribution of the residual thermal stress within the core was numerically studied with a finite element model of the unit cell, in order to prove the positive contribution of the asymmetric layup on the mechanical properties and study the failure mechanisms of the unit-cell. Composite core samples were manufactured, and their mechanical properties were experimentally evaluated through compression, both out-of-plane and in-plane, and beam flexure tests. Results were compared in terms of specific properties with traditional aluminium honeycomb core, showing large increments of specific compressive strength (+84.6%), in-plane compressive modulus (over +500%), Specific Energy Absorption (+145%) and shear (>20%). The FEM model was validated against experimental compressive results, showing an error below 10%. The results show that the core is suitable for applications in novel high-performance sandwich structures, leading to numerous advantages in comparison to traditional cores, such as higher specific properties, manufacturability of complex sandwich structures and higher adhesion and compatibility with CFRP skins.